The design of a research and educational tool to studythe response of a vehicle suspension system using Matlab/Simulink (Damascus University Journal for engineering sciences, 2021)
In this research, a research and educational tool for studying the sensitivity of the vehicle's suspension system to the properties and parameters of the suspension’s components is developed. This tool is a program that can study different models created using the Matlab/Simulink software package with its various libraries. Different types of models can be analysed, such as differential equation models expressing a mathematical model, block diagrams, or state space models. The tool also enables students to identify the suspension’s components, and its basic design parameters, and choose these parameters. Researchers and students will be able to test their models in terms of response, overshoot, and sensitivity, when conducting simulations in different working conditions.
Keywords: Matlab/Simulink